(untitled) (Annals of Medical Research, 2021)
Aim: The aim of the present study was to investigate the analgesic and anti-inflammatory efficacy of 0.25% flurbiprofen mouthwash, and to evaluate its effect on the parameters related to patient morbidity and early wound healing after periodontal flap surgery.Material and methods: Thirty-two patients (19 females and 13 males), diagnosed with moderate periodontitis and presenting at least one quadrant scheduled for periodontal flap surgery, were randomly allocated to either the flurbiprofen group or the placebo group. The plaque index (PI), gingival index (GI), probing pocket depth (PPD), bleeding on probing (BOP) and clinical attachment level (CAL) were evaluated at baseline and PI and GI were re-evaluated at 30-day follow-up. On postoperative 1, 3, 7, 14 and 30 days, postoperative pain, discomfort, changes in patients’ dietary habits, burning sensation and postoperative swelling were analyzed by using a visual analog scale (VAS). At postoperative 7 days, the early wound healing index was assessed clinically.Results: The mean VAS scores exhibiting postoperative pain were significantly lower in flurbiprofen group compared to placebo group at days 1, 7 and 30 (p0.05). Flurbiprofen group had significantly lower scores compared to the placebo group at 14-day follow-up in terms of changes in patients’ dietary habits (p0.05), as well as burning sensation at the first postsurgical day (p0.05). At 30-day follow-up examination, the mean GI values were significantly higher for the placebo group (p0.05).Conclusion: A postsurgical protocol including rinsing with a 25% flurbiprofen mouthwash revealed better analgesic and anti-inflammatory effect and moreover, had a beneficial impact in terms of patient morbidity after periodontal flap surgery.Keywords: Flurbiprofen; Inflammation; Postoperative Pain; Periodontal Flap Surgery.